Epidemiology of bone stress injuries in Australian high performance athletes: A retrospective cohort study - Ruddick, G. K.; Lovell, G. A.; Drew, M. K.; Fallon, K. E. (Journal of Science and Medicine in Sport, 2019)
Objectives: To examine the epidemiology of bone stress injuries in an elite sports institute. Design: Retrospective cohort study at the Australian Institute of Sport. Methods: A retrospective analysis of the clinical records contained within the Australian Institute of Sport Athlete Management System electronic database was performed. Records with Orchard Sports Injury Classification System codes relating to bone stress injuries and stress fractures were reviewed and descriptive statistics relating to sport, site of injury, athlete age, sex and activity were analysed. Results: In the three-year period January 2014-2017, 11,942 injuries were recorded across 48 sports. 181 bone stress injuries (0.15% of all injuries) were recorded across 16 sports. BSIs in the foot and lumbar spine were the most common accounting for 30% and 23% of all the reported BSIs respectively. Gymnasts had a high frequency of lumbar spine stress injuries (n = 24, 51%) and rowers had a high frequency of rib stress injuries (n = 22, 88%). The most common location for stress injuries, equally distributed across a variety of sports, were in the foot (n = 54, 30%). Female athletes recorded more BSIs than males. Conclusion: Across a three-year period, 0.15% of injuries were related to bone stress injuries. Almost double the cases were recorded in female athletes. Sport specific injury sites were observed in the dataset.